Transcriptomic Identification of a Unique Set of Nodule-Specific Cysteine-Rich Peptides Expressed in the Nitrogen-Fixing Root Nodule of Astragalus sinicus - Wei, Feng; Liu, Yuan; Zhou, Donglai; Zhao, Wenlong; Chen, Zhennan; Chen, Dason; Li, Youguo; Zhang, Xue-Xian (Molecular plant-microbe interactions, 2022)
Legumes in the inverted repeat-lacking clade (IRLC) each produce a unique set of nodule-specific cysteine-rich (NCR) peptides, which act in concert to determine the terminal differentiation of nitrogen-fixing bacteroid. IRLC legumes differ greatly in their numbers of NCR and sequence diversity. This raises the significant question how bacteroid differentiation is collectively controlled by the specific NCR repertoire of an IRLC legume. Astragalus sinicus is an IRLC legume that forms indeterminate nodules with its microsymbiont Mesorhizobium huakuii 7653R. Here, we performed transcriptome analysis of root and nodule samples at 3, 7, 14, 28 days postinoculation with M. huakuii 7653R and its isogenic ∆ bacA mutant. BacA is a broad-specificity peptide transporter required for the host-derived NCRs to target rhizobial cells. A total of 167 NCRs were identified in the RNA transcripts. Comparative sequence and electrochemical analysis revealed that A. sinicus NCRs (AsNCRs) are dominated by a unique cationic group (termed subgroup C), whose mature portion is relatively long (>60 amino acids) and phylogenetically distinct and possessing six highly conserved cysteine residues. Subsequent functional characterization showed that a 7653R variant harboring AsNCR083 (a representative of subgroup C AsNCR) displayed significant growth inhibition in laboratory media and formed ineffective white nodules on A. sinicus with irregular symbiosomes. Finally, bacterial two-hybrid analysis led to the identification of GroEL1 and GroEL3 as the molecular targets of AsNCR067 and AsNCR076. Together, our data contribute to a systematic understanding of the NCR repertoire associated with the A. sinicus and M. huakuii symbiosis. [Formula: see text] Copyright © 2022 The Author(s). This is an open access article distributed under the CC BY-NC-ND 4.0 International license .